Jornalismo em vídeo para jovens: o caso da BBC News Brasil no YouTube - Lobo, Ana Cristina Oliveira (2020)
Traditional journalism goes through one of its biggest crisis, causing most of its viewers to go digital. This dissertation consists of analyzing five journalistic videos published on the BBC News Brasil YouTube channel in March 2019. In this work, the videos are analyzed in order to identify characteristics of this journalistic product and show which of these narratives can lead to a greater involvement with the new digital audiences especially the young audience. To do so, retrieve a theoretical framework on concepts such as online journalism, narrative, audiovisual journalistic narrative, digital narrative, or YouTube, a BBC Brasil News and youth media consumption to contextualize and understand the object of study. As for the methodology, we will use the pragmatic analysis of the journalistic narrative developed by Motta, the works of Renato Essenfelder that use this methodology and the support of the practical manual of “Qualitative Research with Image and Sound Text” by Bauer & Gaskell. An analysis of the object will feature the results of the literature review and interview with journalist Silvia Salek, creator and director of the project that includes the corpus videos. The expected result is to understand if this format can be replicated and made up of innovative online journalism practice.